Spectrum of Lesions Found During Endoscopic Retrograde Cholangiopancreatography in Patients with Obstructive Jaundice - Mudassar Ashraf, Madiha Abbas, Fareeha Abbas, Tehreem Shafqat, Abdul Qadoos, Muhammad Ammad Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of malignant and benign lesion in patients presenting with obstructive jaundice. Study Design: Cross sectional study Place and duration of study: Department of Medicine, Lahore General Hospital from 1st November 2016 to 30th April 2017. Methodology: One hundred and fifty patients from indoor as well as outpatient department were enrolled. All the patients of any gender with age between 25-60 years were included. Patients was considered as case of obstructive jaundice if serum bilirubin level >1.2mg/dl and blockage in the bile duct (>50mm narrowing) confirmed by CT scan. Later on patient was advised for biopsy of the bile duct so that the lesion could be categorized weather it is malignant or benign. Results: The mean age was 42±10.50 years. Ninety six (64%) were female and 54 (36%) were male cases. One hundred and twenty one (80.7%) were benign tumor while 29 (19.3%) were malignant. According to sub-types, bile duct was in 91(60.7%) and stricture in 30(20%). Conclusion: There is high frequency of benign tumor among the patients with the obstructive jaundice and hence it is needed to evaluate all such cases with this condition.